Lessons learned from conducting six multi-country mixed-methods effectiveness research studies on water, sanitation, and hygiene (WASH) interventions in humanitarian response - Lantagne, Daniele (BMC Public Health, 2021)
BACKGROUND: Provision of safe water, sanitation, and hygiene (WASH) to affected populations in humanitarian emergencies is necessary for dignity and communicable disease control. Additional evidence on WASH interventions is needed in humanitarian settings. Between 2008 and 2019, we completed six multi-country, mixed-methods effectiveness studies in humanitarian response on six different WASH interventions. In each evaluation, we conducted: key informant interviews; water point observations and water quality testing; household surveys with recipients, including survey and water quality testing; focus group discussions; and/or, secondary data analysis. The research questions were: “What is the effectiveness of [intervention] in reducing the risk of diarrhea/cholera transmission; and, what programmatic factors lead to higher effectiveness?” DISCUSSION: In all six multi-country, mixed-methods evaluations, policy-relevant outcomes were obtained. We found, in our individual research results, that: interventions could reduce the risk of disease in humanitarian contexts; this reduction of risk did not always occur, as there were large ranges in effectiveness; and, implementation factors were crucial to intervention effectiveness. When collaboratively reviewing our research process across evaluations, we found strategies for successfully conducting this research included: 1) working with partners to identify and evaluate programs; 2) rapidly obtaining approvals to deploy; and, 3) conducting research methodologies consistently. Personal connections, in-person communication, trust, and experience working together were key factors for success in identifying partners for evaluation. Successes in evaluation deployment occurred with flexibility, patience, commitment of adequate time, and understanding of processes; although we note access and security concerns in insecure contexts precluded deployment. Consistent and robust protocols, flexibility, and a consistent researcher on the ground in each context allowed for methodological consistency and high-quality results. CONCLUSIONS: In conclusion, we have found multi-country, mixed-methods results to be one crucial piece of the WASH evidence base in humanitarian contexts. This is particularly because evaluations of reductions in risk from real-world programming are policy-relevant, and are directly used to improve programming. In future, we need to flexibly work with donors, agencies, institutions, responders, local governments, local responders, and beneficiaries to design safe and ethical research protocols to answer questions related to WASH interventions effectiveness in humanitarian response, and, improve WASH programming.